2019
DOI: 10.1590/1414-431x20198429
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes and effects of regular low-intensity exercise on gait, balance, and oxidative biomarkers in the spinal cord of Wistar rats

Abstract: The present study aimed to analyze age-related changes to motor coordination, balance, spinal cord oxidative biomarkers in 3-, 6-, 18-, 24-, and 30-month-old rats. The effects of low-intensity exercise on these parameters were also analyzed in 6-, 18-, and 24-month-old rats. Body weight, blood glucose, total cholesterol, and high-density lipoprotein (HDL) cholesterol were assessed for all rats. The soleus muscle weight/body weight ratio was used to estimate skeletal muscle mass loss. Body weight increased unti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 39 publications
1
13
1
Order By: Relevance
“…However, the study limitation relates to the lack of investigation into the extent of injury and current recovery status. In addition, previous animal studies have shown that the ability for balance decreases with age (Silveira et al, 2019), and no such correlation was found in this study. Additional research is needed to analyze the differences between balance and performance, and age and sex in professional athletes.…”
Section: Discussioncontrasting
confidence: 98%
“…However, the study limitation relates to the lack of investigation into the extent of injury and current recovery status. In addition, previous animal studies have shown that the ability for balance decreases with age (Silveira et al, 2019), and no such correlation was found in this study. Additional research is needed to analyze the differences between balance and performance, and age and sex in professional athletes.…”
Section: Discussioncontrasting
confidence: 98%
“…To characterize the effect of aging on brain biomarkers, 47 intact 3-monthold male Wistar rats were obtained from a colony maintained by the Universidade Federal do Rio Grande do Sul. In the laboratory, the rats were housed in groups of three per conventional cage, maintained at 22 ± 2°C, exposed to a 12-h light/dark photoperiod, and provided free access to food and water, as previously described by Silveira et al (17). Briefly, six (n=6) of the rats were acclimated for one week and euthanized by decapitation.…”
Section: Experimental Animalsmentioning
confidence: 99%
“…The animals were classified as young adult (3 months), adult (6 months), middle-aged (18 months), young elderly (24 months), and old (30 months) (17). These ages were chosen because they correspond to human ages of 18, 45, 60, and 75 years, respectively (17,18).…”
Section: Experimental Animalsmentioning
confidence: 99%
See 2 more Smart Citations